2016
DOI: 10.1017/s1478951516000560
|View full text |Cite
|
Sign up to set email alerts
|

How much psychological distress is experienced at home by patients with palliative care needs in Germany? A cross-sectional study using the Distress Thermometer

Abstract: A significant proportion of patients treated at home reported symptoms of distress. The most oft-mentioned problems were physical and emotional in nature. The findings of our study highlight the importance of creating new concepts and structures in order to address the psychosocial needs of patients in home care with palliative needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
1
14
1
5
Order By: Relevance
“…Validation in a palliative care setting is important, because the properties of an instrument as a screening tool depend partly on the population in which it is investigated (Rouse, 2007). In a former study (Kü ttner et al, 2016), we demonstrated that the DT has a high degree of sensitivity and acceptability in persons at the end of life.…”
Section: Introductionmentioning
confidence: 82%
“…Validation in a palliative care setting is important, because the properties of an instrument as a screening tool depend partly on the population in which it is investigated (Rouse, 2007). In a former study (Kü ttner et al, 2016), we demonstrated that the DT has a high degree of sensitivity and acceptability in persons at the end of life.…”
Section: Introductionmentioning
confidence: 82%
“…41 One of the tools was use to assessed the needs of home-based palliative care patients specifically. 64…”
Section: Resultsmentioning
confidence: 99%
“…All other sociodemographic and medical variables showed no statistically significant differences. 10 The response and dropout rate were relatively high. However, there are inherent difficulties in recruiting patients in palliative care due to frailty, deterioration, and death.…”
Section: Discussionmentioning
confidence: 99%
“…The problem list (PL) consists of 38 problems commonly experienced by patients with cancer grouped into 5 categories. 5,10,22 Respondents were instructed to indicate whether any of the items listed were a problem in the previous week by selecting “yes” or “no.” The PL may also suggest the appropriate professional support for each patient. We used the NCCN Guidelines version 2.2013, slightly modified by skipping the item “ability to conceive children” (accepted by the NCCN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation